Activation of Dopamine 4 Receptor Subtype Enhances Gamma Oscillations in Hippocampal Slices of Aged Mice - Wang, Yuan; Jin, Yi-Kai; Guo, Tie-Cheng; Li, Zhen-Rong; Feng, Bing-Yan; Han, Jin-Hong; Vreugdenhil, Martin; Lu, Cheng-Biao (Frontiers in Aging Neuroscience, 2022)
Aim: Neural network oscillation at gamma frequency band (γ oscillation, 30-80Hz) is synchronized synaptic potentials important for higher brain processes and altered in normal ageing. Recent studies indicate that activation of dopamine 4 receptor (DR4) enhanced hippocampal γ oscillation of young mice and fully recovered the impaired hippocampal synaptic plasticity of aged mice, we determined whether this receptor is involved in ageing-related modulation of hippocampal γ oscillation. Methods: We recorded γ oscillations in the hippocampal CA3 region from young and aged C57bl6 mice and investigated the effects of dopamine and the selective dopamine receptor (DR) agonists on γ oscillation. Results: We first found that γ oscillation power (γ power) was reduced in aged mice compared to young mice, which was restored by exogenous application of dopamine (DA). Second, the selective agonists for different D1- and D2-type dopamine receptors increased γ power in young mice but had little or small effect in aged mice. Third, the D4 receptor (D4R) agonist PD168077 caused a large increase of γ power in aged mice but a small increase in young mice, and its effect is blocked by the highly specific D4R antagonist L-745,870 or largely reduced by a NMDAR antagonist. Fourth, D3R agonist had no effect on γ power of either young or aged mice. Conclusion: This study reveals DR subtype-mediated hippocampal γ oscillations is ageing-related and DR4 activation restores the impaired γ oscillations in aged brain, and suggests that D4R is the potential target for the improvement of cognitive deficits related to the ageing and ageing-related diseases.